Ab Initio QM/MM Simulation of Ferrocene Homogeneous Electron-Transfer Reaction - Nicholson, Melany Isabel Garcia [UNESP]; Bueno, Paulo Roberto [UNESP]; Feliciano, Gustavo Troiano [UNESP] (American Chemical Society (ACS), 2021)
Here, we demonstrate the feasibility of hybrid computational methods to predict the homogeneous electron exchange between the ferrocene and its oxidized (ferrocenium) state. The free energy for ferrocene oxidation was determined from thermodynamic cycles and implicit solvation strategies within density functional theory (DFT) methods leading to no more than 15% of deviation (in the range of 0.1-0.2 eV) when compared to absolute redox free energies obtained experimentally. Reorganization energy, as defined according to the Marcus theory of electron-transfer rate, was obtained by sampling the vertical ionization/electron affinity energies using hybrid quantum/classical (QM/MM) Born-Oppenheimer molecular dynamics trajectories. Calculated reorganization energies show a subtle but noteworthy dependence with the nature and the localization of the compensating countercharge. We concluded that the adopted hybrid computational strategy, to simulate homogeneous redox reactions, was successfully demonstrated and it further permits applications in more complex systems (required in daily life applications), where the electron transfer occurs heterogeneously.